THE CONCEPTUAL APPROACHES TO ENSURE THE BALANCE OF STATE FINANCIAL RESOURCES - Колодій, Сергій; Гаряга, Леся; Кочума, Інна (Socio-economic relations in the digital society, 2019)
The conceptual approaches to ensuring the balance of financial resources of the state have been proposed in the article. The essence and classification of the balance of financial resources of the state have been researched. The balance of financial resources of the state has been proposed to interpret as a correspondence between the totality of funds received at the disposal of central and local executive authorities in the process of formation of financial resources of the state, and the totality of funds directed to different purposes during their use. The indicators of the balance of financial resources of the state have been determined: balance of the consolidated budget; the volume of public debt; balance in the Single Treasury Account (STA). The basic general and special provisions of the concept of institutional regulation of the balance of financial resources of the state have been substantiated. Some aspects of the special provisions of the concept of institutional regulation of the balance of financial resources of the state have been described in detail.The key problems of formation, implementation, balancing and ensuring uninterrupted financing of the state financial resources have been highlighted. Proposals have been developed to take measures and use appropriate tools to  improve the management of the state’s financial resources. The balance of financial resources of the state is the basis of stable socio-economic development of the national economy, elimination of its basic macroeconomic imbalances. Therefore, the balance of financial resources of the state should be a subject of the state regulation of the economy. As a result of its effective regulation, it is possible to ensure stable socio-economic development of the state.Implementation of the provisions of the proposed concept will, on the one hand, create a system of containment of unreasonable growth of the budget deficit and public debt, reduce the balance of funds at the STA, and on the other hand, will help reduce the transaction coststhat accompany the process of formation and use of financial resources of the state. The proposed restriction institutions will allow limiting the growth of the consolidated budget deficit, the public debt, and the reduction of the STA balance. This will also affect the level of public debt service costs.
Keywords: the financial resources of the state; indicators of balance of financial resources of the state; the concept of institutional regulation of balance of financial resources of the state; instruments of institutional regulation of financial resources of the state balance